2002
DOI: 10.1073/pnas.052703199
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone attenuates expression of vascular cell adhesion molecule-1 by conversion to estradiol by aromatase in endothelial cells: Implications in atherosclerosis

Abstract: We previously reported that testosterone attenuated atherogenesis in LDLR ؊͞؊ male mice, and that this effect of testosterone was most likely caused by its conversion to estradiol. Estradiol inhibits vascular cell adhesion molecule-1 (VCAM-1) expression, and expression of VCAM-1 is one of the early events in atherogenesis. We assessed the cellular mechanism(s) involved by which testosterone attenuates atherogenesis. We evaluated whether testosterone inhibited TNF␣-induced VCAM-1 expression via its conversion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
2
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(106 citation statements)
references
References 28 publications
4
98
2
2
Order By: Relevance
“…The latter possibility is supported by investigations of other vascular systems, including prostacyclin production in endothelial cells (Mikkola et al 1995) and AT1 receptor gene expression in smooth muscle cells (Nickenig et al 1998), which have revealed that oestradiol may have a maximum effect at 12 h or greater. Endothelial cells can convert testosterone to oestradiol (Mukherjee et al 2002) and it has been suggested that effects attributed to testosterone may be in part a result of its conversion to oestradiol (Sierra-Ramirez et al 2004). However, our observation that testosterone increased the number of adrenomedullin-secreting endothelial cells, and that oestradiol had no significant effect, indicates that the actions of testosterone exhibited here were unlikely to be dependent on its conversion to oestradiol.…”
Section: Discussioncontrasting
confidence: 61%
“…The latter possibility is supported by investigations of other vascular systems, including prostacyclin production in endothelial cells (Mikkola et al 1995) and AT1 receptor gene expression in smooth muscle cells (Nickenig et al 1998), which have revealed that oestradiol may have a maximum effect at 12 h or greater. Endothelial cells can convert testosterone to oestradiol (Mukherjee et al 2002) and it has been suggested that effects attributed to testosterone may be in part a result of its conversion to oestradiol (Sierra-Ramirez et al 2004). However, our observation that testosterone increased the number of adrenomedullin-secreting endothelial cells, and that oestradiol had no significant effect, indicates that the actions of testosterone exhibited here were unlikely to be dependent on its conversion to oestradiol.…”
Section: Discussioncontrasting
confidence: 61%
“…32 This phenomenon may help explain the mechanism by which testosterone may have beneficial effects on the cardiovascular system; however, this effect is mediated by endothelial cell aromatase, converting testosterone to estradiol. 32 IMT-CCA has been shown to be associated with the prevalence of cardiovascular disease 33 and atherosclerotic involvement of other arterial beds, including the coronary arteries, 11,12 and to represent a strong predictor of both myocardial infarction and stroke, 13 even in subjects with no history of cardiovascular disease. 9 Therefore, the results from this study based on IMT-CCA measurements in overweight and obese men may be potentially extrapolated to suggest that hypotesteronemia enhances the susceptibility to atherosclerosis in multiple arterial districts and increases the risk for CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, female sex and estrogens appear to be protective against a range of inflammatory diseases including multiple sclerosis and Alzheimer's to atherosclerosis (Nilsson 2007). Similarly, estrogens appear to suppress the inflammatory responses in experimental models of inflammation in both in vivo and in vitro systems (Nathan et al 1999, Mukherjee et al 2002, Card et al 2006. A significant proportion of this antiinflammatory activity has been attributed to alterations in NO synthesis and activity (Thompson & Khalil 2003, Orshal & Khalil 2004; however, EDHF has also been proposed to play a role.…”
Section: Sex Differences In Vascular Inflammationmentioning
confidence: 99%
“…In addition, there is some evidence suggesting that male sex hormones exert inhibitory effects on leukocyte recruitment. Indeed, testosterone inhibits VCAM-1 mRNA and protein expression in HUVECs, although this action is dependent upon conversion to 17b-estradiol via aromatase activity, an enzyme present in endothelial cells (Mukherjee et al 2002). There is also evidence to suggest that rather than directly affecting adhesion molecule expression, estrogens suppress the expression of specific chemokines (chemoattractant cytokines) that are produced by endothelial cells among other cell types.…”
Section: Sex Differences In Leukocyte Recruitmentmentioning
confidence: 99%